Suseptibilitas Magnetik, pH dan Kandungan Mineral untuk Uji Tingkat Kesuburan Tanah pada Lahan Perkebunan Kemiri di Kecamatan IX Koto Sungai Lasi - Oktavia, Geby Sri Ayu; Pohan, Ahmad Fauzi (Jurnal Fisika Unand, 2025)
Research has been conducted on the value of magnetic susceptibility, pH and mineral content to test the level of soil fertility in Nagari Indudur, District IX Koto Sungai Lasi. Samples were taken at the location of candlenut plantations in two different locations that were suspected of experiencing a decrease in soil fertility. Sampling was taken at 6 points with three depth variations, 30 cm, 60 cm and 90 cm so that 36 samples were obtained. The distance between sampling points is 2 m. Magnetic susceptibility measurements using the MS2B Bartington Susceptibility Meter using two frequencies, namely 0,47 kHz LF (Low Frequency) and 4.7 kHz HF (High Frequency). At location 1, the average value obtained is 181.2089 x10-8 m3/kg, while the average χHF value obtained is 170.5870x10-8 m3/kg. At location 2 the average χLF value obtained is 487.6539x10-8 m3/kg, while the average χHF value obtained is 480.5271 x10-8 m3/kg. with an average pH in both locations of candlenut plantations is acidic. This occurs because of the excess of Si and Al elements that make the plantation soil acidic, as well as the deficiency of Magnesium (Mg) and sulfur, minerals that make candlenut plants experience a decrease in production. Besides that deposition on plantation land is also one of the triggers for soil in the plantation location to experience a decrease in soil fertility.